Spiritual parenting for the community of Tanjung Dayang Selatan Village, Ogan Ilir Regency - Yulasteriyani Yulasteriyani; Randi Randi; Febrimarani Malinda; Cynthia Azhara Putri; Diana Dewi Sartika; Gita Isyanawulan; Yusnaini Yusnaini; Dyah Hapsari (Community Empowerment, 2024)
The laws on child protection and the national education system outline the roles and responsibilities of parents towards their children. However, the reality in Indonesia, particularly in rural areas, reveals that many parents still neglect their children's education and spiritual development, leading to high rates of school dropout and moral decline among children. The objective of community service program is to impart an understanding of Islamic spiritual parenting concepts to the target audience, enabling its application within the community. This community service initiative comprises three main agendas: pre-test, socialization or counseling sessions on family sociology and spiritual parenting, and post-test evaluations. The results of the activity demonstrated a 33% increase in participants' knowledge after engaging in spiritual parenting discussions.